MEDIA KARTU HURUF UNTUK MENINGKATKAN KEMAMPUAN MENIRU HURUF SERUPA PESERTA DIDIK DI RA MATHOLI’UL - Arif Ariyanto, Ika Fitriana (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Flash Card Media to Improve the Ability to Imitate Similar Flashs to Students at RA Matholi'ul Ulum. Learning video from the GPO website "Children Can't Distinguish Similar Flashs" and evaluation results of students who often write the flashs that are similar (b, d, and p) upside down in group A at RA Matholiul Ulum. Writing similar flashs (b, d and p) motivates researchers to improve learning. The analysis of the evaluation results forms the basis of the research. Problem solving is done using flash cards as a medium to improve learning outcomes. So that the purpose of this study is expected to show an increase in the ability to imitate students' similar flashs through flash cards. The research method used is quantitative. This research was conducted in two cycles. The cycle I and cycle II processes are carried out online via the WhatsAppGroup. The number of students in group A at RA Matholiul Ulum is 23. The average value of the evaluation results and the percentage of success of student learning outcomes has increased. The average value in cycle I is BSH (Developing According to Expectations) with a percentage of 56.52% (13 students) and in cycle II BSB (Developing Very Well) with a percentage of 95.65% (22 students) The percentage of success in Cycle I was 34.78% (8 students), and Cycle II was 95.65% (22 students). From this percentage it can be concluded that there is an increase in the use of flash cards on the ability to imitate similar flashs in students.